12
$\begingroup$

Find $f'(0)$ if $f(x)+f(2x)=x\space\space\forall x$

If we assume $f'(0)\in\mathbb R$, then obviously, $f'(0)=\frac{1}{3}$.

But what if we don't assume the derivative exists?

I get this question when I am taking an exam, and I then asked the professor about whether there exist $f$ such that $f'(0)$ doesn't exist but satisfies the condition, but he says he think both exist or not is likely...

What I have tried:

If $f(x)+f(2x)=x\space\space\forall x\in\mathbb R$, $f(x)=\frac{x}{3}$ is the only nice function I have ever thought up$.

If we restrict $dom(f)\in\mathbb R$, I think that any polynomial besides $\frac{x}{3}$ doesn't satisfy the condition, and somethings like $\vert x\vert$ doesn't help neither.

On the other hand, I have tried to think about the equivalence statements with $f(x)+f(2x)=x\space\space\forall x$ in order to prove $f$ must be specific kind of problem s.t.$f'(0)$ exists.

$f(2x)+f(4x)=2x$, so $f(4x)-f(x)=x$.

In general, $$f(2^{2^n}x)-f(x)=x\prod_{k=1}^{n-1}(2^{2^k}+1)\forall n\in\mathbb N, x\in\mathbb R$$

But I don't think this helps.

Can we find $f(2x)-f(x)$ by given condition? I havn't get an idea. But while I am thinking of it, I observe that $g(x)=f(2x)-f(x)$ is on its own satisfying $g(2x)+g(x)=x$.

Will thinking about $f\circ f\circ f\circ f\circ f\circ\dots$ be useful? $f\biggl(f(x)+f(2x)\biggr)+f\biggl(2\bigl(f(x)+f(2x)\bigr)\biggr)=x\space\space\forall x$

Any help will be appreciate. Thank you!

$\endgroup$
  • $\begingroup$ Consider any function with $f(1)=c$ for some $|c|>1$. Then $\lim_{x\to0^+}f(x)$ needn't exist. $\endgroup$ – Simply Beautiful Art Apr 28 '18 at 12:23
6
$\begingroup$

Consider the function $$ f(x)=\left\{\begin{array}{}\sin(\pi\log_2(|x|))+\frac x3&\text{if }x\ne0\\ 0&\text{if }x=0\end{array}\right. $$ That is, the conditions given do not imply that $f'(0)$ exists.

$\endgroup$
5
$\begingroup$

We find $f(0)=0$. On $\Bbb R\setminus \{0\}$ we can define the relation $$x\sim y\:\iff \exists k\in\Bbb Z\colon x=2^ky. $$ This is an equivalence relation and each equivalence class has exactly one representative in $A:=[1,2)\cup(-2,-1]$. Clearly, we can find $f$ satisfying the conditions of the problem statement by defining it arbitrarily on $A$ and then extending it using the functional equation. Note that then the function $g(x):=f(x)-\frac x3$ obeys the functional equation $g(x)+g(2x)=0$ and that consequently $|g(x)|$ is constant on the equivalence classes of $\sim$. In particular, if for some $a\in A$ we have $g(a)\ne 0$, it follows that $g(4^{-n}a)=g(a)$ and $g(2\cdot 4^{-n}a)=-g(a)$ for all $n$ and hence $\lim_{x\to 0}g(x) $ does not exist; consequently, $g'(0)$ and $f'(0)$ do not exist either in that situation. In other words, if we assume that $f$ (and hence $g$) is continuous at $x=0$, it follows that $g\equiv 0$ and $f(x)=\frac x3$. All other starting definitions of $f$ on $A$ lead to a function not differentiable or even continuous at $x=0$. Note that it is well possible to achieve that $x=0$ is the only discontinuity of $f$, one just has to match the interval ends as smoothly as desired.

$\endgroup$
  • $\begingroup$ @AryamanJal Thanks, fixed $\endgroup$ – Hagen von Eitzen Apr 28 '18 at 12:40
  • $\begingroup$ Oh your answer is essentially the same as mine (although yours is definitely better :)), I didn't get a notification when you posted your answer :( $\endgroup$ – orlp Apr 28 '18 at 12:41
-1
$\begingroup$

$f(x)$ is separated into independent subsets defined by equivalence relationship $a = b$ given by $\exists k : 2^k \cdot a = b$.

This is due to two reorderings of the original equation, which can be iterated:

$$f(2x) = x - f(x)$$ $$f(x/2) = x/2 - f(x)$$

Let $f(1) = 1$ by definition. Then we have iteration:

0.5 -0.5
0.25 0.75
0.125 -0.625
0.0625 0.6875
0.03125 -0.65625
0.015625 0.671875
0.0078125 -0.6640625
0.00390625 0.66796875
0.001953125 -0.666015625

It is clear that there is no derivative at $f(0)$.

$\endgroup$
  • $\begingroup$ If there is a formal proof I will be much more appreciate. $\endgroup$ – Tony Ma Apr 28 '18 at 12:41
  • $\begingroup$ @TonyMa See Hagen von Eitzen's answer for a more general and formal approach with the same idea. $\endgroup$ – orlp Apr 28 '18 at 12:43

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.